Controle de constitucionalidade preventivo legislativo: uma análise crítica às decisões das comissões de constituição e justiça das Assembleias Legislativas do Maranhão e Piauí, suas fragilidades e disfunção aos fins de eficácia do controle de constitucionalidade preventivo. - DINIZ, Ingrid Medeiros Lustosa (2018)
The present study reflects the need for more detailed studies on the conduct of the state legislative process, specifically on the work carried out by the Constitutional and Justice Commissions regarding the exercise of preventive legislative review on law-acting constitutionality of the legislative proposals of Complementary Laws . It has as its focus the analysis of the opinions of the Committees on Constitution and Justice of the Legislative Assemblies of Maranhão and Piauí in the period from 2011 to 2014, corresponding to the last legislature. During the conduction of the work, several methodological procedures were used, being this intense bibliographical research, documentary analysis of the Complementary Law projects and the opinions issued by the Commissions of Constitution and Justice and, finally, Content Analysis in the perspective and teaching of Laurence Bardin (1977), allowing the implicit and explicit considerations that contribute to the main objective of this work to be extracted from the opinions. In order to finalize and in the light of the interpretations and inferences obtained by the analysis and research of data, it was considered the importance of implementing the legislative preventive constitutionality control in the scope of CCJs, noting the need to institutionalize a democratic legislative procedure that makes the conscience and importance of its realization possible as a requisite of legitimacy to the entire State Legislative Process.